Effect of low-level laser therapy on proliferation and cytotoxicity of mouse fibroblasts and human fibroblasts: An in vitro study - Mallanagouda B. Patil; Deeksha D. Pai; Shobha Prakash (Journal of Indian Society of Periodontology)
Background: Diode laser is known for its biostimulatory effects on various cell populations such as osteoblasts and fibroblasts. The usage of low-level laser therapy for photobiomodulation depends on its type, emission wavelength, and energy selected. Previously performed in vitro studies have determined its effect on cell proliferation and cytotoxicity; however, the results were inconsistent. Objectives: The objectives of this study were to evaluate and compare diode laser effect on mouse embryonic fibroblasts (MEFs) and human gingival fibroblasts (HGFs) for proliferation and cytotoxicity. Materials and Methods: 32 samples, 16 wells of MEF cells (Group I) and HGF cells (Group II) each with 8 subgroups containing control (no laser irradiation) and experimental (laser irradiated) groups were cultured after being seeded at 4000 cells/ well with 4cm inter-well distance. Experimental group cell cultures were irradiated with a single dose of 810 nm diode laser (energy 1J/cm2, 12.5 mW, 80 s/well) using continuous wave mode after 1 day of incubation. Spectrophotometric analysis was done after 24 h of laser irradiation for cell proliferation and cell cytotoxicity on the 2nd, 3rd, and 7th days on all groups. Results: Human and mouse fibroblast groups showed positive results when irradiated with an 810 nm laser. A hundred percent proliferation was seen for MEF in 7 days and HGF in 2 days. Two percent cytotoxicity was seen on the 2nd and 3rd day in MEF. Increased cell proliferation and minimal cytotoxic effects were seen with diode laser usage. Conclusion: Low-level laser irradiation indicates an increase in cell proliferation with less cytotoxicity on mouse and human fibroblasts.